Developing Remo Asri Kusuma Dance as an Institutional Identity Through Early Childhood Education Students - Dhirgan Grudhowaringin; Gesang Bayu Pamungkas; Astrid Wangsagirindra Pudjastawa (Jurnal Pendidikan dan Penciptaan Seni, 2026)
This research aims to develop a Remo Asri Kusuma dance tutorial video as an enrichment medium for Early Childhood Education (ECE) students in creating new choreographed dances that serve as institutional identities. The study employs the Research and Development (RD) method using the Borg and Gall model, simplified into five primary stages: (1) preliminary study and information gathering, (2) initial product draft development, (3) expert validation (content and media), (4) field testing (small and large groups), and (5) final product revision. Research instruments utilized Likert scale questionnaires to measure media feasibility. The results indicate that the tutorial video is categorized as "Highly Feasible," with an average score of 92% from content experts and 88% from media experts. During the field-testing phase, student responses demonstrated a 90% effectiveness rate in practicing movement varieties independently. The video contains comprehensive material ranging from historical context to the 12 detailed movement varieties of Asri Kusuma, characterized by their bold nature. Through this medium, ECE students are able to adopt traditional movement elements and modify them into new dance works aligned with early childhood developmental characteristics. The implementation of this media is proven effective in enhancing students' choreographic competence while strengthening institutional branding through the preservation of local culture within the ECE environment.